PEMANFAATAN APLIKASI AKUNTANSI DIGITAL DALAM PENYUSUNAN LAPORAN KEUANGAN - Fildza Ayu Safina; Elia Dwi Meisyaroh; Gunawan Aji (Jurnal Akuntansi, 2025)
By analyzing the advantages, drawbacks, and organizational elements affecting the efficacy of digital accounting software, this study seeks to provide a comprehensive understanding of how these tools aid in the creation of financial statements. This paper summarizes current research on digital accounting, user competency, corporate processes, and reporting quality using a qualitative literature review. The findings show that although the effectiveness of digital applications depends on users' accounting abilities, digital literacy, internal controls, and organizational preparedness, they also increase efficiency, decrease manual errors, and improve reporting uniformity. The study also reveals that a lot of sophisticated features are still underutilized because of poor managerial support and insufficient training. Practically speaking, the results emphasize the necessity of robust internal controls, sufficient technology infrastructure, and ongoing user development. The study's unique approach to comprehending the adoption of digital accounting is its comprehensive integration of organizational, technological, and human elements.